Penerapan Green Economy Pada Industri Batik Untuk Tujuan Pembangunan Berkelanjutan Dalam Pendekatan Etika Bisnis - Deny Lesmana Putra; Masfulatul Liliani; Eka Fuji Lestari; Alif Nanda Ayu; Putri Wulandari; Sela Rachmawati; Faqih Ulil Abshor (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2026)
Batik is a national cultural heritage of Indonesia recognized by UNESCO and plays an active role in the industrial sector in Indonesia. Facing problems in processing liquid waste from the production process, especially in the use of textile dyes. This research discusses the management of good and sustainable batik waste using a business ethics and green economy approach. This research uses a qualitative approach by using data collection techniques with interview methods and literature studies in two batik industries, namely PT Pusaka Batik and Batik Winotosastro. The results explained that the implementation of green economy and business ethics is still not optimal due to the limitations of qualified human resources, finance, and technology. However, by applying and combining both principles of business ethics and green economy, it is proven that it can reduce air pollution and make batik waste treatment better. this happens when the batik industry does not only prioritize personal gain but prioritizes the environment and society, it can create sustainable development (SGDs).